Divergent Trends by Patient Age in Racial Disparities in Kidney Transplant Access - Jade Buford; Jessica L. Harding; Mengyu Di; Marciana L. Laster; Kelsey Drewry; Stephen O. Pastan; Rachel E. Patzer (Kidney International Reports, 2025)
Introduction: Although non-Hispanic Black (Black) and non-Hispanic White (White) racial disparities in access to transplantation have decreased over the past 2 decades, it remains unclear whether trends are consistent across all ages and transplant steps. Methods: We identified 1,091,206 White or Black adults initiating dialysis (cohort 1) and 226,703 adults waitlisted (cohort 2) in the United States Renal Data System (USRDS) from 2005 to 2019, followed through 2021. Study outcomes were as follows: (i) waitlisting (among patients on dialysis), (ii) living donor kidney transplant (LDKT) (among patients on dialysis), and (iii) deceased donor kidney transplant (DDKT) (among waitlisted adults). Individuals were grouped into eras (2005–2009, 2010–2014, and 2015–2019) based on dialysis initiation or waitlisting date. Multivariable-adjusted subdistribution hazard models assessed changes in racial disparities, overall and by age (18–29, 30–49, 50–64, and 65–80 years) at kidney replacement therapy (KRT) initiation. Results: Racial disparities in waitlisting among patients on dialysis did not improve between 2005–2009 (0.90; 95% confidence interval [CI]: 0.88–0.92) and 2015–2019 (0.92; 95% CI: 0.90–0.94); P for interaction = 0.11). Among adults aged 18 to 29 years, relative rates of Black-White waitlisting differences worsened from 2005–2009 (0.77; 95% CI: 0.69–0.78) to 2015–2019 (0.68; 95% CI: 0.64–0.72); P = 0.13), whereas disparities among adults aged 30 to 49 years decreased (0.79 ; 95% CI: 0.76–0.81) to 0.89; (95% CI: 0.86–0.92; P < 0.001). Among waitlisted adults, Black (vs. White patients) were less likely to receive a DDKT in 2005–2009 (0.92; 95% CI: 0.89–0.95) but more likely to receive a DDKT in 2015–2019 (1.28; 95% CI: 1.24–1.32); P < 0.001). Black patients on dialysis were less likely to receive LDKT (0.37; 95% CI: 0.35–0.39); this trend persisted over time, with the largest and statistically significant decline among adults aged 65 to 80 years (0.49; 95% CI: 0.42–0.59) to 0.38; (95% CI: 0.33–0.45); P = 0.03). Conclusion: Strategies to improve access to transplantation, especially among younger and older Black adults, should be revisited.